Verfahrensfolge Laserstrahlschneiden und –schweißen: Prozeßführung und Systemtechnik in der 3D-Laserstrahlbearbeitung von Blechformteilen - Hoffmann, Peter (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1992)
Welding of butt joints in bodyshell areas of cars can cause expensive rework operations due to the high heat input with is produced conventional joining technologies. Laser beam welding could be an alternative but the geometry of the formed parts must be very accurate. This can be achieved by using laser instead of shear cutting for the trimming of the formed parts. Aim of the investigations conducted in this work was to define parameters of laser manufacturing operations to enable a failure free combination of both technologie